Hypotension in Nursing Home Residents on Antihypertensive Treatment: Is it Associated with Mortality? - TUFAN ÇİNÇİN, ASLI (ELSEVIER SCIENCE INC, 2021)
Objective: To assess whether low systolic blood pressure (SBP) or diastolic blood pressure (DBP) due to antihypertensive medications might be related to mortality among nursing home (NH) residents. Design: Observational, longitudinal. Setting: Nursing home. Participants: Age >60 years, receiving antihypertensive medications. Measurements: Demographic characteristics, mobility status, number of chronic diseases and drugs, nutritional status, and antihypertensive medications were noted. At the first visit, we recorded blood pressure (BP) measurements of last 1 year, which were measured regularly at 2-week intervals and considered their mean values. SBP and DBP thresholds were analyzed for mortality by ROC analysis. Multivariate Cox regression analyses were performed to determine factors related to mortality. Results: The sample included 253 residents with a mean age of 75.7 +/- 8.7 years, and 66% were male. Residents were evaluated at a mean follow-up time of 14.3 +/- 5.2 months (median: 15) for short-term mortality and 31.6 +/- 14.3 months (median: 40) for long-term mortality. The prevalence of low SBP (<110 mm Hg) and low DBP (<65 mm Hg) was 34.8% and 15.8%, respectively. In follow-up, the shortterm mortality rate was 21.7% (n = 55) and the long-term mortality rate was 42.2% (n = 107). Low SBP (<110 mm Hg) was related to mortality in shortand long-term follow-ups [short-term follow-up: hazard ratio (HR) 3.7, 95% confidence interval (CI) 1.5-8.6, P = .01; long-term follow-up: HR 1.8, 95% CI 1.1-3.0, P = .02], adjusted for age, mobility status, nutritional state, and total number of diseases and drugs. Low DBP (<65 mm Hg) was related to mortality in shortand long-term follow-ups [short-term follow-up: HR 3.0, 95% CI 1.2-7.8, P =.02, long-term follow-up: HR 2.8, 95% CI 1.5-5.2, P = .001], adjusted for age, mobility status, nutritional state, and total number of diseases and drugs. Conclusions and Implications: Systolic hypotension was found in more than one-third of the NH residents receiving antihypertensive treatment. Low SBP and DBP were significant factors associated with mortality. Particular attention should be paid to prevent low SBP and DBP in NH residents on antihypertensive treatment. (c) 2021 AMDA d The Society for Post-Acute and Long-Term Care Medicine.
Keywords: Hypertension; mortality; nursing home; older adults; treatment; HIGH BLOOD-PRESSURE; WALKING SPEED; OLDER; HYPERTENSION; ADULTS; MANAGEMENT; MEDICATIONS; HEALTH; TRIAL; RISK